A Meta‐Analytic Study: The Relationship Between Acculturation and Depression Among Asian Americans. (29th July 2013) - Gupta, Arpana; Leong, Frederick; Valentine, Jeffrey C.; Canada, Dericka D.
Abstract : Acculturation is an important and popular cultural research variable among specific ethnic populations that is used to explain the process of assimilating into the host culture. Acculturation has often been used to account for psychosocial changes and health outcomes and has been used to explain health disparities among ethnic groups. Using Asian Americans as an illustrative ethnic group, the authors see that researchers have highlighted the influence of acculturation on health outcomes. Some researchers suggest that this relationship is positive, whereas others postulate that the opposite is true. Because of the highly complex and divergent findings in the literature, this meta‐analysis addresses the question of how acculturation (as measured by acculturation scales) is related to depression (a specific mental health outcome) among the Asian American population living in North America. Analyses were based on 38 studies. The meta‐analyses reveal that when acculturation is measured as assimilation to the American culture, there is a small but statistically significant negative relationship between acculturation and depression scores. When acculturation is measured as orientation to the Asian culture, the relationship between acculturation and depression scores is also negative, but not statistically significant.